Gateway sink placement for sensor node grid distribution in lora smart city networks - Nur Aishah Bt. Zainal; Mohamed Hadi Habaebi; Israth Jahan Chowdhury; Md Rafiqul Islam; Jamal I. Daoud (Institute of Advanced Engineering and Science, 2019)
Low Power Wide Area Network (LPWAN) is a type of wireless communication network designed to allow long range communications at a low bit rate among things (connected objects), such as sensors operated on a battery. It is a new technology that operates in unauthorized spectrum which designed for wireless data communication [1]. It is used in Internet of Thing (IoT) applications and M2M communications. It provides multi-year battery lifetime and is intended for sensors and applications that need to transmit only a few information over long distances a few times per hour from different environments. In order to have an insight of such long range technology, this paper evaluates the performance of LoRa radio links under shadowing effect and realistic smart city utilities node grid distribution. Such environment is synonymous to residential, industrial and modern urban centers. The focus is to include the effect of shadowing on the radio links while attempting to study the optimum sink node numbers and their locations for maximum sensor node connectivity. Results indicate that the usual unrealistic random node distribution does not reflect actual real-life scenario where many of the these sensing nodes follow the utilities infrastructure around the city (e.g., street light posts, water and gas delivery pipes,…etc). The system is evaluated in terms of connectivity and packet loss ratio.